A new genus of burrowing and cave-dwelling millipedes (Diplopoda: Polydesmida: Dalodesmidae) from Tasmania, Australia - Mesibov, Robert (Zootaxa, 2005)
Atalopharetra johnsi n. gen., n. sp. and A. bashfordi n. sp. are forest-dwelling, burrowing millipedes with overlapping distributions in southern and southwestern Tasmania. A. clarkei n. sp. and A. eberhardi n. sp. are troglomorphic, cavernicolous species from limestone karst near Ida Bay and Precipitous Bluff, respectively, within the ranges of A. bashfordi and A. johnsi.